Whole body MRI by MY-RADS for imaging response assessment in multiple myeloma - Christina Messiou; Nuria Porta; Dow-Mu Koh; Angela Riddell; Katherine Downey; James Croft; Leonora Conneely; Georgina Hopkinson; Alina Dragan; Tommy Brown; Simon Stern; Betty Cheung; et al. (Blood Cancer Journal)
Abstract Minimal residual disease (MRD) testing has underpinned the evaluation and expansion of therapeutic options for patients with multiple myeloma (MM). Imaging is essential for evaluating residual disease status, overcoming sampling errors inherent with other MRD modalities. The accuracy of whole-body MRI (WB-MRI) has led to its incorporation into MM diagnostic imaging guidelines. We report here on the prospective iTIMM trial (image-guided theranostics in MM; NCT02403102), designed to evaluate imaging residual disease using contemporary, functional WB-MRI as per MY-RADS protocol. In iTIMM, 70 MM patients planned to undergo autologous stem cell transplantation ASCT in newly diagnosed MM or at first relapse, underwent WB-MRI before start of induction and at day 100 post-ASCT. Patients with residual disease post-ASCT (RAC2 or higher) had shorter progression-free survival (median 24 months, 95% confidence interval (CI): 19–41 vs. 42 months, 95% CI: 37–not evaluable (NE), log-rank p = 0.013; hazard ratio (HR) 2.09 (95% CI: 1.15–3.78) and overall survival (median 47 months, 95% CI: 30.9–NE vs. NE (95% CI: NE–NE), p = 0.002, HR = 5.45 (95% CI: 1.67–17.87) than those without (RAC1). Imaging response also refined the prognostic association of bone marrow MRD and serological response. Our results support WB-MRI implementation for evaluation of residual disease alongside conventional laboratory-based assessments.